(untitled) (The Research of Medical Science Review, 2024)
Neutrophil to lymphocyte ratio (NLR) is a marker that reflects the state of systemic inflammation. A high NLR was reported to be associated with short term mortality. However, little is known about the association between high NLR and short-term mortality in patients with end stage kidney disease (ESKD).To determine the diagnostic accuracy of NLR values in predicting the short-term mortality in ESKD patients keeping actual mortality as gold standard. This cross-sectional validation study was conducted at Department of General Medicine, Fauji Foundation Hospital Rawalpindi from March 2024 to September 2024. A total of 200 male and female patients with age between 20 to 70 years and presented with ESKD were enrolled for this study. Subsequently, a complete blood count (CBC) test was conducted and NLR values were determined. Patients with NLR >8.2 were labelled as high NLR. Short-term mortality waslabelled as positive if death of ESKD patient occurs due to any cause with-in 30 days of the enrollment to the study. Collected data was analyzed using SPSS software and diagnostic accuracy was determined. Mortality occurred in 69 patients (34.5%). Among patients who were predicted for 30 days mortality due to high NLR, 75% (n=60) experienced mortality, whereas only 7.5% (n=9) of those with low NLR values experienced mortality. 30.0% of the patients were true positive, 55.5% were true negative, 10.0% of the patients were false positive and only 4.5% were false negative. It was noticed that sensitivity of prediction of 30 days mortality by high NLR value was 86.96% while specificity was 84.73%, positive predictive value was 75%, negative predictive value was 92.5% and overall accuracy was 85.5%.This research identifies the NLR as a reliable predictor of 30-day mortality in patients with ESKD, demonstrating high sensitivity, specificity, and diagnostic accuracy. It also serves as an economical instrument for the early stratification of risk and prompt intervention in the management of ESKD.